Analisis dan Pengembangan Sistem Pengelolaan Digital Signage berbasis Media TV pada Aplikasi Perguruan Tinggi - Ibrahim Syafiq Musyaffa; Amalia Rahmah (Jurnal Informatika Terpadu, 2021)
Digital signage is one of the electronic media that serves to display information. STT Terpadu Nurul Fikri uses campus television as a digital information board (digital signage) to display various information such as video announcements, student activities, and campus profile videos. However, digital signage content management has not been maximized due to manual methods using a flash connected directly to the television. This causes the content that can be displayed to be limited to video formats only. In this study, we built an information system for managing digital signage named Nufi TV. This web-based system builds using the PHP CodeIgniter framework. We developed the Nufi TV digital signage system by going through stages, starting from collecting data, conducting analysis, designing the system display, implementing, testing with black-box and UAT methods, and evaluating the results achieved. Some of the features that we have succeeded in building in this system are video, lecture schedule, and running text. However, some features that have not successfully create are the content submission feature and image viewer.